2015
DOI: 10.3758/s13415-015-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

Binding neutral information to emotional contexts: Brain dynamics of long-term recognition memory

Abstract: There is abundant evidence in memory research that emotional stimuli are better remembered than neutral stimuli. However, effects of an emotionally charged context on memory for associated neutral elements is also important, particularly in trauma and stress-related disorders, where strong memories are often activated by neutral cues due to their emotional associations. In the present study, we used event-related potentials (ERPs) to investigate long-term recognition memory (1-week delay) for neutral objects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 104 publications
5
53
0
Order By: Relevance
“…We propose, therefore, that an emotional stimulus retrieves its emotional context together with its temporal context, thereby helping the recall of further emotional items that share the same emotional context, while hindering recall of stimuli with a different (neutral) context (Polyn et al, 2009). This interpretation is directly supported by evidence that objects that have been paired just once with an emotional context are associated with enhanced LPP magnitude and enhanced old-new effects during a subsequent recognition test (Ventura-Bort, Low, et al, 2016;Ventura-Bort, Löw, et al, 2016). Further, this interpretation is also supported by findings that participants who recall mixed lists of emotional and neutral stimuli tend to recall emotional stimuli closely after other emotional stimuli, demonstrating semantic clustering effects around the emotional category (Long et al, 2015;Talmi et al, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 74%
“…We propose, therefore, that an emotional stimulus retrieves its emotional context together with its temporal context, thereby helping the recall of further emotional items that share the same emotional context, while hindering recall of stimuli with a different (neutral) context (Polyn et al, 2009). This interpretation is directly supported by evidence that objects that have been paired just once with an emotional context are associated with enhanced LPP magnitude and enhanced old-new effects during a subsequent recognition test (Ventura-Bort, Low, et al, 2016;Ventura-Bort, Löw, et al, 2016). Further, this interpretation is also supported by findings that participants who recall mixed lists of emotional and neutral stimuli tend to recall emotional stimuli closely after other emotional stimuli, demonstrating semantic clustering effects around the emotional category (Long et al, 2015;Talmi et al, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 74%
“…We propose, therefore, that an emotional stimulus retrieves its emotional context together with its temporal context, thereby helping the recall of further emotional items that share the same emotional context, while hindering recall of stimuli with a different (neutral) context (Polyn et al, ). This interpretation is directly supported by evidence that objects that have been paired just once with an emotional context are associated with enhanced LPP magnitude and enhanced old‐new effects during a subsequent recognition test (Ventura‐Bort, Low, Wendt, Dolcos et al, ; Ventura‐Bort, Löw, Wendt, Moltó et al, ). Further, this interpretation is also supported by findings that participants who recall mixed lists of emotional and neutral stimuli tend to recall emotional stimuli closely after other emotional stimuli, demonstrating semantic clustering effects around the emotional category (Long, Danoff, & Kahana, ; Talmi et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…In another study, Dolcos & Cabeza () observed that enhanced elaborated processing during encoding, as indexed by LPP amplitude, predicted better long‐term memory performance for emotional information. Consistent with this, we have recently observed that objects paired with emotional, relative to neutral contexts, elicited enhanced electrophysiological correlates implicated in mnemonic retrieval processing (Ventura‐Bort et al ., ). The present study, thus, indicate that faster enhanced perceptual and elaborative processes of neutral information bound to emotional compared to neutral contexts might also promote memory storage (Dolcos & Cabeza, ; Weymar et al ., ; Ventura‐Bort et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Each participant viewed three (out of six) different sets, consisting of a total of 144 neutral objects. Half of the neutral objects (144) were used in a recognition memory task that occurred 1 week later (published elsewhere, see Ventura-Bort et al, 2016). One hundred and forty-four background scenes -48 pleasant, 48 neutral and 48 unpleasantwere selected from the International Affective Picture System (IAPS; Lang et al, 2008) as UCS.…”
Section: Stimulus Materialsmentioning
confidence: 99%